Mixed Method Research of Intra-Organizational Trust Model Based on Collective Reaction (Case Study: Tehran Education) - Saeed Azadeh; Ali Akbar Farhangi; Seyed Mohammad Zahedi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Trust is a vital and essential factor for individual and organizational success that increases order, stability and predictability of the future. The aim of this study is to design a model of intra-organizational trust through collective action in education in Tehran. Experts including senior managers, professors and leading consultants in the field of management of the organization were considered as the statistical community. Nine experts were interviewed in-depth using the snowball sampling method. In the quantitative phase, all education staff in Tehran were considered as a community. Three hundred seventy-seven were selected as a statistical sample. Data collection tools in the qualitative phase of the research were in-depth and unstructured interviews with experts. The data were analyzed based on the data theory method (open, axial and selective coding). In the quantitative phase of the research, a closed and researcher-made questionnaire was used. SPSS, LISREL and smart-PLS software were used for descriptive and inferential analysis. The results showed that collective action within and between the structural layers of the organization through the redesign of organizational processes can increase intra-organizational trust in education in Tehran.